Design and implementation of electrical system morphing wing flight control on prototype light aircraft - Christian Leonard; Erwan Eko Prasetiyo; Ikbal Rizki Putra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This journal discusses the implementation and testing of the electrical morphing wing system on light aircraft prototypes, namely technology on the wing to increase the value of aerodynamic efficiency on the wing surface with experimental methods based on knowledge obtained from various literature sources. Using a configuration of eight servo actuators arranged in parallel for the aileron and flap functions as well as setting and control with a six-channel Flysky-FSi6 remote to control the movement of the master and slave aileron actuators as well as the flap function on the morphing wing. The design includes the layout of the actuator, setting commands on the remote and wiring system electrical components. Other aspects such as rib design, mechanism and material selection affect the overall distribution of motion produced by the servo actuator. Through the design of the electrical system morphing wing design on the prototype aircraft, it is proven to be able to support the needs of the morphing wing motion mechanism with the concept of an arrangement of eight actuators in parallel on the rib morphing wing. It is hoped that the concept of the morphing wing can be implemented and further developed so that it can be used on full-scale aircraft.